Model Perencanaan Tata Ruang Wilayah menggunakan Spatial Temporal Autocorrelation (Studi Kasus: Kabupaten Jayawijaya) - Kogoya, Waiki Elkius; Prasetyo, Sri Yulianto; Sulistyo, Wiwin (Diponegoro University, 2024)
Jayawijaya Regency faces various challenges in the use of land tenure status in urban planning areas (RTRW). This study focuses on the RTRW Spatial Pattern Plan in Wamena Urban on changes in land tenure with a spatial temporal autocorrelation (STA) approach. The results showed that there were two spatial patterns formed in the Wamena Urban Area, namely cluster patterns and dispersed patterns. Cluster patterns are formed in airports, urban areas, flat woodland agriculture, local protection/LIPI plantations, and river boundaries. Dispersed patterns are formed in community plantations and scrubs, rural settlements, wetland agriculture, slope dryland agriculture, and mining. The results of the analysis showed that cluster patterns in the Airport, Urban, Flat Dryland Agriculture, Local Protection/LIPI Plantations, and River Border areas showed significant changes in land tenure status. Climate change, infrastructure development, and population growth are some of the factors causing these changes. Meanwhile, dispersed patterns in community plantations/shrubs, rural settlements, wetland agriculture, slope dryland agriculture, and mining showed no significant change in land tenure status. This is due to factors such as conflicts over customary rights to land ownership. This study provides an overview of spatial patterns of changes in land tenure status in the Wamena Urban Area. The results of this research can be used as a basis for the formulation of land management policies and strategies in the region.